Gramática visual no jornalismo: os significados ao pé da letra: estudo de caso sobre capas da publicação francesa Charlie Hebdo - Berbert, Eugenia Celia Victal Barbosa (2019)
Magazines play na important communicative role in the propagation of information. The cover of the magazine is na element of great relevance in order to arouse the reader's interest, capable of distinguishing between a vehicle and its message among many others. Thecovers are composed of images and texts tha tcomplement each other and give meaning to the statement.This dissertation aims to discuss the value and peculiarities of the verbal-visual language of the covers of the Charlie Hebdo French magazine, bringing covers of national and international magazines as examples of the use of graphic and verbal resources throughout the research and seeking to perceive the editorial interferences in relation to the creative practice of the magazine cover. We used three covers of CharlieHebdo from the years 2015, just before and shortly after the terrorist attack, as well as the cover of the vehicle one year after the attack. In particular, we aimed to demonstrate the narrative predictions and characteristics of the covers of the Charlie Hebdo magazine and to indicate how the intentions of the verb-visual language applied to the covers in questionare conceived. In order to achieve this goal, we list the subsequent categories of research, starting with the conceptual framework based in particular on Bahktin and the circle: compositional form, style, dialogism, the meand visual grammar from the stand point of Gunther Kress and Van Leeuwen, where we will analyze elements that constitute the verbo-visual language, suchas: colors, layout, letter types and their size, as well as images and their deformation. A study from the point of view of Pierce's semiotics will also serve as abasisfor seeking the understanding intendedin this study, among other authors. As a hypothesis, weseek to discover, from the basic concepts of journalistic genres, whether Charlie fits into any of them, considering the constant use of the charge element, even between genres, or has such specific characteristics that make it extrapolate any formal definitions making it sui generis.